The Impact of Orthography on Text Production in Three Languages: Catalan, English, and Spanish - Llaurado, Anna; Dockrell, Julie E. (Frontiers in Psychology, 2020)
Learning to write effectively is key for learning and participation in social communities. In English, transcription skills (handwriting and spelling) constrain written production at the early stages of learning to write. The effect of transcription diminishes with age, when reading skills enhance text production. Less is known about how transcription and reading interact with writing in other languages. In this study, we explore the relationships between spelling, reading and the length and quality of written text produced by primary school children speaking three different languages: Catalan, English, and Spanish. These languages are good test cases for models of writing development as they contrast orthographically and morphologically. Participants produced a written narrative text and completed standardized assessments of handwriting, spelling, reading decoding, and reading comprehension. Language had a significant effect on text production measures: young Spanish children produced longer texts which were of higher quality than the other two cohorts. They also produced the lowest number of spelling errors both at the root and for affixed morphemes. By contrast, the English children produced the highest number of both types of errors. The Catalan children did not differ significantly from their English peers for root level spelling but produced significantly fewer spelling errors at the affixed morpheme level. To test how transcription and reading skills impact on text production skills, we conducted regression analysis for each language. Different patterns of relationships between transcription, reading and text production emerged. In Catalan only handwriting fluency accounted for significant variance in text productivity and quality. By contrast, for the English children significant variance in productivity was accounted for by reading and handwriting fluency and for text quality by handwriting fluency and spelling. For the Spanish children reading skills were the significant factor for text quality. No other models were significant. Implications for developmental models of writing development are discussed.